2020
DOI: 10.51302/tce.2020.371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación constructiva-cronométrica como herramienta para evaluar el aprendizaje en línea y presencial

Abstract: Se presenta una forma innovadora de aproximar la evaluación del aprendizaje desde una visión cognitiva. Para ello, se ejemplifica el uso de un modelo de medición constructiva-cronométrica del aprendizaje a través de varios dominios del conocimiento y se ilustra la forma en que este tipo de evaluación proporciona diversos indicadores de organización y estructura del esquema de conocimiento que el estudiante presenta antes y después de haber cursado una materia. La evidencia obtenida sugiere que el modelo de eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The NSN and Gephi analyses indicated that the participants entered the course with a previous-knowledge schema or a knowledge pre-schema (see Table 1 and Figure 3). The existence of a knowledge pre-schema has been observed in other studies (e.g., Morales-Martinez, Lopez-Perez et al, 2020); however, the organization and structure are rudimentary. This finding suggests that students generally have a vague schema about the knowledge they will acquire in their courses, and it is based on this schema that they reorganize and reconfigure the information they will learn in class.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The NSN and Gephi analyses indicated that the participants entered the course with a previous-knowledge schema or a knowledge pre-schema (see Table 1 and Figure 3). The existence of a knowledge pre-schema has been observed in other studies (e.g., Morales-Martinez, Lopez-Perez et al, 2020); however, the organization and structure are rudimentary. This finding suggests that students generally have a vague schema about the knowledge they will acquire in their courses, and it is based on this schema that they reorganize and reconfigure the information they will learn in class.…”
Section: Discussionsupporting
confidence: 64%
“…Changes in the configuration of the schematic structure have been observed in other studies that have used the C3-LEM (Morales-Martinez, Lopez-Perez et al, 2020;Morales-Martínez, Mezquita-Hoyos et al, 2018;Urdiales-Ibarra et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The cognitive sciences' theoretical, experimental, and mental representation paradigms help measure the cognitive changes due to academic learning. In this regard, the Chronometric Constructive Cognitive Learning Evaluation Model (C3-LEM) (Lopez-Ramirez et al, 2014;Morales-Martinez, 2020;Morales-Martinez et al, 2015, 2017Morales-Martinez & Lopez-Ramirez, 2016), is a functional cognitive approach for assessing the cognitive changes produced by learning in the student's minds. This cognitive learning evaluation model works under human serial and parallel information processing principles.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, cognitive psychology offers a wide range of measurement tools to help build these new evaluation systems. For example, the Chronometric Constructive Cognitive Learning Evaluation Model or C3-LEM (Lopez et al, 2014;Morales-Martinez, 2020;, 2017Morales-Martinez & Lopez-Ramirez, 2016;Morales-Martinez, Lopez-Perez et al, 2020;Morales-Martinez, Hedlefs-Aguilar et al, 2021;, is an initiative that proposes the combined use of research techniques and digital tools in cognitive science to explore the mechanisms of knowledge acquisition and to promote student learning. This model is based on the principles and laws of human cognitive function from the Human Information Processing (HIP) and Parallel Distributed Processing (PDP) approach.…”
Section: Introductionmentioning
confidence: 99%